Neoadjuvant atezolizumab + chemotherapy for resectable NSCLC: 3-year clinical update of phase II clinical trial results and translational findings - Benjamin Izar; Justin F Gainor; Mark M Awad; Codruta Chiuzan; Anjali Saqi; Catherine A Shu; Katja Schulze; Brian S Henick; Naiyer A Rizvi; Samyukta Mallick; Yohanna Georgis; Peter D Koch; et al. (Journal for ImmunoTherapy of Cancer)
Introduction Neoadjuvant chemoimmunotherapy has achieved overall survival (OS) benefit for patients with resectable non-small cell lung cancer (NSCLC). Here, we present outcomes after 3 years of follow-up from the first reported study of neoadjuvant atezolizumab+chemotherapy.Methods This open-label, multicenter single-arm investigator-initiated phase II study conducted at three US hospitals tested up to four cycles of atezolizumab, carboplatin, and nab-paclitaxel prior to surgery. Major pathological response (MPR, primary endpoint) was previously reported; here, we report 3-year disease-free survival (DFS), OS, and clinical characteristics of patients developing brain metastases (BM) with integrated data from tumor genomics, gene expression, and quantitative immunofluorescent measurement of immune markers.Results Of 30 enrolled patients, 29 were taken to the operating room. 26 underwent R0 resection, with 17 experiencing MPR (10 pCR). With a median follow-up of 39.5 months, the median OS was 55.8 months, and the median DFS was 34.5 months. Landmark OS at 36 months was 77%. Among 14 patients with recurrent disease, 6 patients had BM. Patients whose tumors had mutations in STK11 and KEAP1 did not have a significantly higher incidence of BM. Reduced copy number of STK11 and KEAP1, both residing on chromosome 19p, was observed in ~1/3 of tumors. Reduced CN of STK11 was significantly associated with worse pathological response and incidence of BM.Conclusions Consistent with recent phase III studies, 3-year OS data with neoadjuvant atezolizumab+chemotherapy was associated with prolonged PFS and OS. Establishing associations between STK11 and KEAP1 genomic alterations and key clinical outcomes in early-stage NSCLC requires further study.